Beyond the survival and death of the deltamethrin-threatened pollen beetle Meligethes aeneus: An in-depth proteomic study employing a transcriptome database - Erban, Tomas; Harant, Karel; Chalupnikova, Julie; Kocourek, Frantisek; Stara, Jitka (Journal of proteomics, 2017)
UNLABELLED: Insecticide resistance is an increasingly global problem that hampers pest control. We sought the mechanism responsible for survival following pyrethroid treatment and the factors connected to paralysis/death of the pollen beetle Meligethes aeneus through a proteome-level analysis using nanoLC coupled with Orbitrap Fusion™ Tribrid™ mass spectrometry. A tolerant field population of beetles was treated with deltamethrin, and the ensuing proteome changes were observed in the survivors (resistant), dead (paralyzed) and control-treated beetles. The protein database consisted of the translated transcriptome, and the resulting changes were manually annotated via BLASTP. We identified a number of high-abundance changes in which there were several dominant proteins, e.g., the electron carrier cytochrome b5, ribosomal proteins 60S RPL28, 40S RPS23 and RPS26, eIF4E-transporter, anoxia up-regulated protein, 2 isoforms of vitellogenin and pathogenesis-related protein 5. Deltamethrin detoxification was influenced by different cytochromes P450, which were likely boosted by increased cytochrome b5, but glutathione-S-transferase ε and UDP-glucuronosyltransferases also contributed. Moreover, we observed changes in proteins related to RNA interference, RNA binding and epigenetic modifications. The high changes in ribosomal proteins and associated factors suggest specific control of translation. Overall, we showed modulation of expression processes by epigenetic markers, alternative splicing and translation. Future functional studies will benefit. BIOLOGICAL SIGNIFICANCE: Insects develop pesticide resistance, which has become one of the key issues in plant protection. This growing resistance increases the demand for pesticide applications and the development of new substances. Knowledge in the field regarding the resistance mechanism and its responses to pesticide treatment provides us the opportunity to propose a solution for this issue. Although the pollen beetle Meligethes aeneus was effectively controlled with pyrethroids for many years, there have been reports of increasing resistance. We show protein changes including production of isoforms in response to deltamethrin at the protein level. These results illustrate the insect's survival state as a resistant beetle and in its paralyzed state (evaluated as dead) relative to resistant individuals.
Keywords: brouci; Pyrethrins; transkriptom; Cytochrome b5; insekticidy; Transcriptome; rezistence k insekticidům; hmyzí proteiny; Databases, Genetic; Epigenetics; pyl; Pathogenesis-related protein 5; Ribosomal proteins; proteomika; Insecticide Resistance; Pollen; databáze genetické; Animals; nitrily; Anoxia up-regulated protein; zvířata; Coleoptera; Insecticides; pyrethriny; Insect Proteins; Nitriles; Proteomics; Pesticide resistance